Cardiac activity in walleye (Sander vitreus) during exposure to and recovery from chemical anaesthesia, electroanaesthesia and electrostunning. Issue 1 (24th May 2022) - Reid, Connor H.; Raby, Graham D.; Faust, Matthew D.; Cooke, Steven J.; Vandergoot, Christopher S.
Abstract: Handling and conducting invasive procedures are necessary for aspects of fisheries science, invariably inducing a stress response and imposing energetic demands on fish. Anaesthesia or immobilisation techniques are often used in an attempt to mitigate stress and improve welfare, yet these also come with their own impacts on post‐release recovery. Here, the authors investigated whether changes in cardiac activity (heart rates over time, heart rate maxima, and scopes) differed in adult walleye ( Sander vitreus ) anaesthetised with AQUI‐S® 20E (eugenol), electroanaesthetised with a transcutaneous electrical nerve stimulation (TENS) unit or electrostunned with a commercially developed stunning unit. This experiment was divided into two trials. In the first trial, fish were implanted with heart rate loggers and left to recover for c. 4 days. In the second trial, fish were implanted with heart rate loggers, given 3 days to recover and re‐exposed to their initial treatments (excluding surgery). Post‐treatment cardiac activity was quantified for both trials. Although highly variable across individuals, the authors found no significant differences in heart rate changes over time or recovery times among treatments. Maximum heart rates were consistent among treatment groups, yet significant differences in heart rate scope provided further evidence of strong interindividual variation in the second trial. Based on these results, the authors did not identify any welfare‐relevant differences or concerns associated with one treatment over another. Further investigations of the relationships between measures of cardiac function and other physiological stress markers would be beneficial towards identifying best practices for fish handling in fisheries science.